Comparison of the men's and the women's pole vault at the 2000 Sydney Olympic Games - Schade, F.; Arampatzis, A.; Brüggemann, G. P.; Komi, P. V. (Journal of Sports Sciences, 2004)
The aim of this study was to identify differences between elite male and female pole vaulters in terms of their mechanical energy and angular momentum. The vaulter's total mechanical energy and angular momentum were calculated from the three-dimensional kinematic data of the pole vault finals at the Sydney 2000 Olympic Games. The development of total, kinetic and potential energy showed similar characteristics for men and women. The initial energy of the vault, the energy at maximum pole bend position and the final energy were significantly higher for male athletes (P <0.05), while the energy gain produced by the athletes during the vault showed no significant differences (male vaulters 5.88 +/- 1.02 J.kg(-1), female vaulters 5.74 +/- 1.63 J.kg(-1)). Time-related parameters relating to pole bending and recoiling also showed no significant differences (P <0.05). In contrast to the male vaulters, the female vaulters did not show a free upward flight phase. The angular momentum was significantly higher for the female vaulters during the initial pole bend and during the bar clearance (P <0.05). We conclude that the pole vaulting technique of female elite athletes is not a projection of the technique of male elite vaulters at a lower jump height, but rather a different way of jumping and interacting with the elastic pole. The current technique of elite female pole vaulters still has potential for further improvement.